Investigation of Thermal Stress Arising in a Graphene Neutral Density Filter for Concentrated Photovoltaic System - Mussad M. Alzahrani; Anurag Roy; Senthilarasu Sundaram; Tapas K. Mallick (Energies, 2021)
As an excellent heat spreader candidate, graphene attracts considerable interest concerning its application in concentrated photovoltaic (CPV) systems. The consequences of employing a graphene-coated neutral density (GCND) filter to mitigate concentrated light impact adequately. Hence, the temperature for a concentrated photovoltaic system is reported in this work. A systematic thermal characterisation study was carried out using three different thickness-based GCND filters. Interestingly, using the GCND filter, the focal spot temperature remained considerably lower than that of the incident temperature for a more extended period. The graphene coating orientation further influenced the temperature gradient behaviour of the focal spot and incident temperature. The thermal and electrical results depended on the GC samples’ thickness and emplacement, leading to dramatic differences in their respective photovoltaic performance. As a base substrate of the GCND filter, the low-iron glass suffered extreme thermal stress under concentrated solar irradiance. This thermal stress phenomenon on the GCND filter was further analysed. This study suggests that using GCND leads to lower temperature maintenance of the CPV focal point, which minimises the PV cell thermal stress. However, the GCND filter also experienced considerable thermal stress during the CPV experiment.